Hybrid Encryption for Radio Frequency Identification in Healthcare System: Object-Oriented Analysis and Design Approach - BC, Amanze; CC, Ononiwu; EL, Eleberi; UL, Chilaka (International Journal of Computer Sciences and Engineering, 2020)
Data security is one of the main issues to be considered when the transmission is through wireless communication. The problems that necessitated this research are: eavesdropping, impersonation attack and the security of the back end database. The aim of this study is to develop an Encryption Standard for RFID database. The objective is to develop a system that can: Provide a Hybrid encryption using Advanced Encryption Standard and Elgamal Encryption Algorithm to secure and validate the integrity of patients’ database. The methodology adopted for this paper is the Object Oriented Analysis and Design methodology (OOADM). In this paper, five text files of different sizes were used to conduct four experiments, where a comparison of three algorithms Advanced Encryption Standard (AES), Elgamal Encryption algorithm and the new Chamberlin Hybrid Encryption Standard (CHES)was performed. Performance of encryption algorithm was evaluated considering the following parameters: encryption time, decryption time and size of encrypted file. Based on our analysis, the new hybrid encryption algorithm has a better performance with respect to the security of patients’ records and the confidentiality of their records is high. The new algorithm will ensure integrity of medical records of patients against potential hackers. This thesis proposes a hybrid encryption algorithm for security of database and protection in radio frequency identification system using an advanced encryption standard and elgamal encryption as a cryptographic primitive. This algorithm protects high-valued sensitive health records against malicious users. With the developed system, one can provide a proof for each record stored in the database of the RFID system because it is sufficiently robust to withstand replay attack, eavesdropping attack and backward traceability. All records are randomized and each tag has its own unique identification data. One recommend this work to Nigeria Police Force and higher institutions to enable them leverage on the digital technology to enhance security.